Alcohol and delirium tremens: effects of average number of drinks per day and beverage type. (17th February 2019) - Sørensen, H. J.; Holst, C.; Knop, J.; Mortensen, E. L.; Tolstrup, J. S.; Becker, U.
Abstract : Objective: Associations of amount of alcohol intake and beverage type with the risk of delirium tremens (DT) have not been studied. This longitudinal study investigated if the average number of drinks per day and beverage type predict DT. Methods: A cohort of 3 582 alcohol‐dependent men and women aged 19–82 without previous DT were interviewed about alcohol intake and beverage type at baseline in 1994–2005 and followed through record linkage in Danish nationwide registers to identify incident DT. Data were analyzed by means of Cox regression models. Results: An average number of drinks per day of 20–30 or >30 was associated with hazard ratios (HRs) of 1.38 (95% CI 1.03–1.84) and 1.64 (95% CI 1.19–2.27) relative to the reference category (1–9 drinks). Independently of amount consumed and covariates (age, gender, civil status and work status), beverage type (spirits vs. mixed alcohol) was associated with a HR of 1.63 (95% CI 1.08–2.46). Male gender was robustly associated with increased risk (HR = 1.62 (95% CI 1.25–2.08). Conclusions: In alcohol‐dependent men and women, daily alcohol intake above a threshold of 20 beverages or 240 g alcohol and a preference for spirits increase the risk of developing DT.